OPTIMIZING BIO-COAGULANTS FOR BREWERY WASTEWATER TREATMENT USING RESPONSE SURFACE METHODOLOGY (Nigerian Journal of Technology, 2017)
Coag-flocculation process was used to treat brewery effluent stream with Detarium Microcarpum seed powder (DMSP) and oyster dried shell powder (ODSP) as coagulants. The proximate analyses of the coagulants were obtained using AOAC standard method. Percentage moisture, ash, fat, crude protein, crude fiber and carbohydrate content were determined for both coagulants. Jar test experiments were employed for the coag-flocculation process and response surface methodology (RSM) optimize the process. A box-Behnken design (BBD) of Design Expert 6.0.8, implementing RSM was used to evaluate the effects and interactions of three factors: coagulant dosage, pH and stirring time on the treatment efficiency. The optimal conditions obtained were coagulant dosage of 100.53mg/L, pH of 2.001 and stirring time of 24.47mins with 90.44% solid particle (SP) removal (desirability value of 1.0) and coagulant dosage of 104.19mg/L, pH of 3.34 and stirring time of 27.54 with 96.55% SP removal (desirability value of 1.0) for DMSP and ODSP, respectively. These agree reasonably with the experimental optimum for both coagulants. A determination coefficient, R2, of 97 and 98%; F-value of 45.8056 and 55.3045; and prob.-value of 1.92E-07 and 2.39E-07 for DMSP and ODSP respectively were used to evaluate the model adequacy.RSM has been demonstrated to be appropriate approach for the optimization of this process.http://dx.doi.org/10.4314/njt.v36i4.16